Exploring Bacterial Communities and Functions in Phytophagous Halyomorpha halys and Predatory Arma chinensis - Hongmei Cheng; Xiaoyu Yan; Changjin Lin; Yu Chen; Le Ma; Luyao Fu; Xiaolin Dong; Chenxi Liu (Insects)
The phytophagous Halyomorpha halys (Hemiptera: Pentatomidae) is a global agricultural pest that damages many crops. Conversely, the predatory Arma chinensis (Hemiptera: Pentatomidae) shows promise as a biological control agent against lepidopteran and coleopteran pests. Halyomorpha halys and A. chinensis are closely related species with different feeding habits, as confirmed via genomic and morphological analyses. However, no study investigating the implications of these differences has been reported. Herein, 16S rRNA sequencing technology was employed to analyze the microbiota diversity and function in different tissues (salivary glands, gut, sperm, and ovaries) of H. halys and A. chinensis to elucidate these differences from a microbial perspective. Additionally, the adult male-to-female ratio in A. chinensis organs was statistically similar, while that in H. halys was not. Based on the dominance of the symbionts in the two bug species, we inferred that Sodalis is involved in reproduction and digestion in A. chinensis, while Spiroplasma and Pantoea play essential roles in H. halys reproduction and digestion. We analyzed the data on the microbial diversity of two bug species, laying a foundation for further understanding microbial symbiosis in A. chinensis and H. halys, which may inform the development of biological control strategies.